A IMAGEM NO LIVRO DIDÁTICO DE LÍNGUA INGLESA: REFLETINDO SOBRE MULTIMODALIDADE NO ENSINO BILÍNGUE - PEREIRA, SÂMARA CELYNE DA CUNHA (2023)
The present work aims to present and analyze the relevance of the images in an English language textbook used in an early elementary year’s bilingual program that is primarily based on the Content and Language Integrated Learning (CLIL) approach. Based on the studies by Kress & van Leeuwen (1996), Coyle, Hood & Marsh (2010), as well as contributions from authors such as Haugen (1953), Baker (2011), Harmers and Blanc (2000), Norman (2004), and Dalton-Puffer (2013), a case study was conducted to analyze the images present in a textbook, with their functions and guidelines for classroom use, as described in the teacher's guide. The results revealed four functions of images in the textbook: a) images that contribute to the meaning of language; b) images that reinforce or complement the text; c) images that cause emotions in the reader; and d) images that can provide meaning independently of the text. It was concluded that images play a crucial role in the second language learning process, depending on the specific function, objective, and context in which they are employed. These images are particularly relevant in teaching English to children, as they can provide a more meaningful teaching and learning experience supported using multimodality and the Content and Language Integrated Learning (CLIL) approach.